South Asia symposium on pneumococcal disease and the promise of vaccines – Meeting report. Issue 23 (17th May 2016) - Kumar, Rakesh; Arora, Narendra; Santosham, Mathuram
Abstract: Despite the licensure of the pneumococcal conjugate vaccine (PCV) in the US and other Western countries for over 14 years, as of September 2014 only 4 South Asian countries were using PCV in their universal immunization program. To generate momentum toward addressing this issue a "South Asia symposium on pneumococcal disease and the promise of vaccines" was organized just prior to the 9th international symposium on pneumococci and pneumococcal diseases held in India recently. Leading scientists, program managers, and decision makers including ministry officials from the region participated in the meeting. The participants discussed available data on pneumococcal disease burden in South Asia, surveillance methods, efficacy and safety of pneumococcal conjugate vaccines (PCV), the status of PCV introduction, programmatic challenges in introducing PCV and available data on the impact of PCV in South Asia and globally. There was a strong consensus that available data on disease burden and the global experience with PCV justified the introduction PCV in all Asian countries in order to accelerate the gains in child survival in the region.